STUDYING OF THE INFLUENCE OF THIRD MOLARS ON THE DENTOALVEOLAR ARCH - M. A. Mavlonova; D. A. Suleymanova; G. A. Muratova; S.Z. Sotivoldiyeva (Journals Park Publishing, 2023)
The influence of the third permanent molars on the dentoalveolar arches remains in the focus of attention of many researchers. The objective of the present study was to elucidate the influence of the third permanent molars on the dentoalveolar arches. Material and methods. We analyzed the photographs and X-ray images obtained from 58 patients in the course of the orthodontic correction and during the retention period in whom the formation of the third permanent molars was completed. We registered changes that developed in the dentoalveolar arches during this time. The methods of logical analysis were employed. Results. In the case of lack of space, third permanent molars transmit the force generated in the course of formation of their roots and eruption onto the anteriorly located teeth. This force may cause bone resorption in the anteriorly located teeth as well as their displacement and/or that of the third molars. The magnitude of the displacement is a function of both the resulting force acting on the teeth and its direction. Conclusion. The occlusal force exerts an influence on the teeth location. Difficult eruption of the wisdom teeth may substantially increase this force and lead, in the case of occlusal interference between the eyeteeth, to the deformation of the mandibular dental arch in the region of the eyeteeth. The immature teeth occupy in the alveolar process the optimal position for the current anatomical and functional state. The extraction of the immature third molars prior to the onset of mineralization of their crown is minimally injurious
Keywords: dentoalveolar arch, third molar, semi-retention.